2008
DOI: 10.1016/j.urology.2008.05.057
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Matched-Control Analysis of Adjuvant and Salvage Postoperative Radiation Therapy for pT3-4N0 Prostate Cancer

Abstract: OBJECTIVES It is unclear whether postoperative salvage radiation therapy (SRT) and early adjuvant radiotherapy (ART) after radical prostatectomy lead to equivalent long-term tumor control. We studied a group of patients undergoing ART by comparing them with a matched control group undergoing SRT after biochemical failure. METHODS Using a multi-institutional database of 2299 patients, 449 patients with pT3-4N0 disease were eligible for inclusion, including 211 patients receiving ART and 238 patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 23 publications
(19 reference statements)
1
39
1
5
Order By: Relevance
“…5 Patients with favorable characteristics for all five features had a 470% chance of biochemical control 4 years after salvage radiation therapy. 6 The effectiveness of adjuvant radiation therapy in preventing PSA relapse and metastasis has been described in several retrospective 7,8,9 and prospective 10,11 studies, with some studies also attempting to determine factors that would predispose patients to a positive response to adjuvant therapy. [12][13][14] The long-term follow-up of the Southwest Oncology Group adjuvant radiation therapy trial (SWOG 8794/RTOG 9019) with 12-year data 15 16 Given the modest duration of this study's follow-up, the long-term risk of metastatic disease is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…5 Patients with favorable characteristics for all five features had a 470% chance of biochemical control 4 years after salvage radiation therapy. 6 The effectiveness of adjuvant radiation therapy in preventing PSA relapse and metastasis has been described in several retrospective 7,8,9 and prospective 10,11 studies, with some studies also attempting to determine factors that would predispose patients to a positive response to adjuvant therapy. [12][13][14] The long-term follow-up of the Southwest Oncology Group adjuvant radiation therapy trial (SWOG 8794/RTOG 9019) with 12-year data 15 16 Given the modest duration of this study's follow-up, the long-term risk of metastatic disease is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] In one study, adjuvant RT was only found to be beneficial over salvage RT if the side effects were negligible, emphasizing the importance of side effects on treatment timing. 18 In addition, long-term follow-up from the European Organization for Research and Treatment of Cancer (EORTC) trial 22911 has shown that clinical progression-free survival rates previously reported with adjuvant RT were no longer clinically significant; moreover, in patients over 70, adjuvant RT had a detrimental effect on progression-free and overall survival.…”
Section: Complications Of Radiotherapy After Prostatectomymentioning
confidence: 99%
“…2,4,5 Salvage RT, performed later and triggered by biochemical recurrence, has been shown to be beneficial in several retrospective analyses. [6][7][8][9] Although the results of retrospective trials comparing adjuvant and salvage RT favour adjuvant RT, [10][11][12][13] no prospective randomized trials have been completed. The timing of postoperative RT remains controversial and treatment toxicity should be one of the factors considered.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, this question (and the question of the optimal duration of adjuvant androgen deprivation therapy) is currently being tested in the intergroup RCT RADICALS which is open in more than 20 centres across Canada. Patients with any high-risk features should be considered for this trial.…”
Section: Andrew Loblaw MD Frcpcmentioning
confidence: 99%